A Study on Legume-Based Noodles as Staple Food for Office Workers - Sumali, Brian; Yoshimoto, Joto; Kobayashi, Hiroto; Yamada, Mei; Maeda, Tetsuya; Mitsukura, Yasue (Frontiers in Nutrition, 2022)
This study aims to verify the effects of "legumes-based noodles" as staple food for lunch, specifically: blood glucose, cognitive function tests, kansei value, work questionnaires, typing, and body weight. During the experiment, data acquisition was divided into two: the intervention group (legumes-based noodle) with those from the control group (regular lunch), with similar menu except the staple food. The intervention group resulted in significantly lower blood glucose AUC and lower maximum blood glucose levels during the afternoon work hours on weekdays. In addition, the kansei value “concentration” decreased at the end of the workday in the control group compared to before and after lunch but did not decrease in the intervention group. Furthermore, the number of typing accuracy was higher in the intervention group than in the control group, and the questionnaire responses for "work efficiency" and "motivation" were more positive. These results suggest that eating legumes-based noodles may lead to improved performance of office workers